Analisis Pengaruh Kemampuan Komunikasi Pemimpin, Kompetensi Individu Pemimpin dan Motivasi Terhadap Kinerja Karyawan pada Industri Biro Jasa Tour & Travel di Makassar - Murniady Muchran (Universitas PGRI Yogyakarta, 2023)
This study intends to analyze the effect of communication skills of leaders, individual competence of leaders and motivation on employee performance either partially or simultaneously. This research is quantitative research with multiple linear regression analysis techniques carried out by utilizing the help of the SPSS program. Data collection techniques using questionnaires and interviews as complementary data sources. Samples were taken from employees of 30 tour & travel service bureau companies in Makassar who are members of ASITA. The results of this study concluded that partially the communication skills of leaders, individual competence of leaders and motivation have a positive impact on employee performance. Simultaneously the impact of the leader's communication skills and individual competence of the leader has a positive impact on employee performance.